Application of Green Building Concept (Rainwater Harvesting) at Menara Cibinong Apartment - Anantika, Tiara (Journal of Architectural Research and Education, 2019)
The implementation of Green Building criteria is relatively new in plumbing installation. Bogor regency is a city of rain, rainfall data of 18.09 mm/day so that the concept of green buildings can be applied with the use of rain water. Consequently, the integration of these criteria into the design process has the potential to change the design process itself. The implementation of the green building criteria into the conventional design process will be discussed in this paper. The concept of this project is to design an apartment that has 5 towers of 20 floors each with a green building concept. To achieve this goal, the Green Building criteria has been implemented since the beginning of the design process until the detailing process on the end of the project. Several studies were performed throughout the design process, such as Conceptual reviews, where several professionally proved theories related to plumbing installation systems and used for a reference. Rainwater harvesting can save 3,48% of clean water from water sources.Keywords—Plumbing Installation, Green Building, Rainwater Harvesting